1990
DOI: 10.1021/bi00472a030
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of 1,2-dibromo-3-chloropropane: evidence for the formation of reactive episulfonium ion intermediates

Abstract: The nematocide and soil fumigant 1,2-dibromo-3-chloropropane (DBCP) is a carcinogen and a mutagen and displays target-organ toxicity to the testes and the kidney. It has been proposed that both cytochrome P-450 mediated activation and glutathione (GSH) conjugation pathways are operative in DNA damage and organotropy induced by DBCP. To determine the chemical mechanisms involved in the bioactivation of DBCP and to assess a role for an episulfonium ion intermediate, the mechanism of formation of GSH conjugate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Deuterium substitution for hydrogen at the terminal bromomethyl carbon atom of tris(2,3-dibromopropyl)phosphate (Tris-BP) and 1,2-dibromo-3-chloropropane (DBCP) resulted in 5-to 6-fold decreased rates of mutagenicity and formation of the highly mutagenic metabolite, 2-bromoacrolein (Nelson et al, 1984;Omichinski et al, 1988). However, evidence from investigations with deuterated and methylated analogs suggested that tissue organ damage in rats caused by Tris-BP and DBCP resulted from GSH conjugation as the major rate-limiting reaction (Dybing et al, 1989;Pearson et al, 1990). Both pathways may be involved in organ toxicity since sequential metabolism of Tris-BP and DBCP by oxidation and glutathione conjugation forms reactive metabolites of these compounds as well (Fig.…”
Section: Use Of Deuterium Isotope Effects To Probe P450 Reactionsmentioning
confidence: 99%
“…Deuterium substitution for hydrogen at the terminal bromomethyl carbon atom of tris(2,3-dibromopropyl)phosphate (Tris-BP) and 1,2-dibromo-3-chloropropane (DBCP) resulted in 5-to 6-fold decreased rates of mutagenicity and formation of the highly mutagenic metabolite, 2-bromoacrolein (Nelson et al, 1984;Omichinski et al, 1988). However, evidence from investigations with deuterated and methylated analogs suggested that tissue organ damage in rats caused by Tris-BP and DBCP resulted from GSH conjugation as the major rate-limiting reaction (Dybing et al, 1989;Pearson et al, 1990). Both pathways may be involved in organ toxicity since sequential metabolism of Tris-BP and DBCP by oxidation and glutathione conjugation forms reactive metabolites of these compounds as well (Fig.…”
Section: Use Of Deuterium Isotope Effects To Probe P450 Reactionsmentioning
confidence: 99%
“…[11][12][13] In this paper, we present preliminary evidence on the enhancement effect of a-and b-CD (CDs) on the rate of oxidation of GSH. [14][15][16] A reaction mechanism is suggested based on data resulting from collision-induced dissociation of (CD/GSH) complexes in an ion trap.…”
mentioning
confidence: 99%
“…Time response reaction was performed with 128 µL of 2-B-2-MP, 2,3-dBPe, 2-BP, BE and 2-IP at a time interval of 8h for 0, 8,16,24,32,40 and 48 h at the physiological condition, respectively. At the end of the reaction 300 µL of 1 M HCl was added and centrifuged for 10 min at 13,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Short-chain halogenated alkanes, which we utilized for the study of deguanylation of guanine based-nucleosides, have been widely used industrially as chemical intermediates, extraction solvents, degreasing compounds, copolymer cross-linking agents, or have been reported to be mutagenic and carcinogenic. [8][9][10][11][12][13][14][15][16][17] Among the sixteen different halogenated alkanes, we observed massive deguanylation of nucleosides by 2-bromo-2-methylpropane (2-B-2-MP), 2,3-dibromopropene (2,3-dBPe), 2-bromopropane (2-BP), bromoethane (BE) and 2-iodopropane (2-IP). …”
Section: Introductionmentioning
confidence: 99%